Chromatic equivalence classes of certain generalized polygon trees - Peng, Yee Hock; Little, Charles H. C.; Teo, Kee Leong; Wang, H. (Elsevier Science, 1997)
Let P(G) denote the chromatic polynomial of a graph G. Two graphs G and H are chromatically equivalent, written G ∼ H, if P(G) = P(H). Let g denote the family of all generalized polygon trees with three interior regions. Xu (1994) showed that g is a union of chromatic equivalence classes under the equivalence relation '∼'. In this paper, we determine infinitely many chromatic equivalence classes in g under '∼'. As a byproduct, we obtain a family of chromatically unique graphs established by Peng (1995).